Relationship between Digital Stress and Employee Performance with Psychological Capital as Moderator - Oktavia, Gissa Aulia; Zamralita (Analitika: Jurnal Magister Psikologi UMA, 2024)
This study aims to explore the relationship between digital stress and employee performance, as well as the role of psychological capital as a moderator in this relationship. The research employs a quantitative method involving 231 participants working at Institution X, where information and communication technology (ICT) is an integral part of employees' daily tasks. The variables measured in this study include digital stress, employee performance, and psychological capital. The study uses the Digital Stressor Scale (DSS) to measure digital stress, the Individual Work Performance Questionnaire (IWPQ) to measure employee performance, and the Psychological Capital Questionnaire to measure psychological capital. The findings reveal that employees' psychological capital is in the high category (M= 4.430), and employee performance is also high (M= 3.284), while digital stress is in the moderate category (M= 4.005). Further analysis indicates that psychological capital acts as a moderator in the relationship between digital stress and employee performance.